Implementation of a structured surgical quality improvement programme - Spence, Richard Trafford (Department of Surgery, 2017)
As surgery assumes a greater position in the global health agenda, the need to not only improve access to surgical care but also improve the quality of surgical care, is paramount. Surgical quality improvement programmes have been shown to reduce morbidity and mortality following surgery. A key first step to the design and implementation of a structured surgical quality improvement programme is the collection and analysis of high-quality data. To quote Dr. Margaret Chan, the director general of the World Health Organisation, '…the real need (in global health) is to close the data gaps, especially in low and middle-income countries, so that we no longer have to rely heavily on statistical modeling for data on disease burden.' In this thesis it was hypothesized that emerging m-Health technology, defined as medical and public health practices supported by the use of mobile devices, would provide a solution to close such data gaps. Various m-Health applications were used to develop three databases describing the outcomes of major surgery performed within the Cape Metro West health district during the study period. After reviewing the design and analytical rationale of the American College of Surgeons National Surgical Quality Improvement Programme and Trauma Quality Improvement Programme, these de novo databases were used to develop three quality improvement programmes designed for local implementation: The Essentials programme for general and vascular surgery, a Procedure-targeted programme and a trauma quality improvement programme. Key to these programmes was the derivation and validation of prediction rules which reliably estimate the probability of an adverse outcome following major surgery in a risk-adjusted manner. Such rules promote internal and external benchmarking over time to identify opportunities for quality improvement and critically appraise the impact of any corrective action implemented. In order to improve the quality of surgical care we provide, a continuous cycle of monitoring, assessment, and management should be performed routinely. This thesis provides some guidance of how this can be done within the Cape Metro West health district.